Toxicidade e potencial antitumoral do derivado espiro-acridínico (E)-1'-((4- clorobenzilideno)amino)-5'-oxo-1',5'-diidro-10H-espiro[acridina-9,2'-pirrol]- 4'-carbonitrila (AMTAC-06) - Duarte, Sâmia Sousa (2021)
Cancer comprise an esemble of diseases characterized by uncontrolled cell growth and metastatic potential. Current chemotherapy treatments have limitations, mainly due to toxicity and the development of tumor resistance. Considering that acridine compounds are reported as promising anticancer agents, this study aimed to investigate the antitumor activity and toxicity of the new synthetic spiro-acridine compound (E)-1'-((4-chlorobenzylidene)amino)-5'- oxo-1',5'-dihydro-10H-spiro[acridine-9,2'-pyrrole]-4'-carbonitrile (AMTAC-06), selected after pharmacological screening. In vitro antitumor activity and cytotoxicity was evaluated by the MTT assay, using tumor cells (HCT-116, HeLa, MCF-7, PC-3, MDA-MB-231, SK-MEL-28, HL-60) and non-tumor cells (L929, HaCat, PBMC). AMTAC-06 induced higher cytotoxicity in colorectal carcinoma cells, HCT-116 (IC50, or half-maximal inhibitory concentration, of 12.62 µM, in 72 hours), and reduced the viability of non-tumor cells (HaCaTIC50: 17.87 µM; L929IC50: 26.15 µM; PBMCIC50: 7.89 µM). However, AMTAC-06 was less cytotoxic compared to the standard drug doxorubicin (HCT-116IC50: 2.57 µM; HaCaTIC50: 0.28 µM; PBMCIC50: 0.05 µM). In order to elucidate its mechanisms of action in vitro, the effects on cell cycle, apoptosis and on the production of reactive oxygen species (ROS) in HCT-116 cells (15 and 30 µM AMTAC-06, after 48 hours) were evaluated. AMTAC-06 induced an increase in the sub-G1 fraction and cell cycle arrest in the S phase (p <0.05). Morphological characteristics of apoptosis, such as membrane blebbing formation, apoptotic bodies, chromatin condensation and nuclear fragmentation, were observed by confocal microscopy. Simultaneously, there was an increase in the number of staining cells with annexin V (p <0.05), characterizing apoptosis. There was also a reduction in the production of ROS (p <0.05), which suggests an antioxidant effect. In vivo, AMTAC-06 toxicity was investigated in Swiss mice (Mus Musculus) and in zebrafish (Danio rerio), and the antitumor activity was studied using the Ehrlich Ascites Carcinoma (EAC) model. AMTAC-06 did not induce toxicity in zebrafish embryos/larvae (LC50, or mean lethal concentration, higher than 126.2 µM) or in mice (LD50, or mean lethal dose, higher than 5000 mg/kg, i.p.). Genotoxicity was assessed by the micronucleus test on peripheral blood of mices, and it was observed that AMTAC-06 (2000 mg/kg, i.p.) did not show genotoxicity. In a EAC model, AMTAC-06 (12.5 mg/kg, i.p.) reduced the viability and the total peritoneal tumor cells (p <0.05), as well as the microdensity of the peritumoral vessels (p <0.05), indicating antiangiogenic effect. In addition, there was an increase in the levels of cytokines TNF-α and IL-1β, as well as a reduction in INF- in the peritoneal fluid, characterizing an immunomodulatory action associated with antitumor activity. The analysis of biochemical, hematological and histological parameters in animals transplanted with Ehrlich and treated with AMTAC-06 (12.5 mg/kg, i.p.) did not show toxicity. In conclusion, the new spiro-acridine derivative AMTAC-06 has antitumor activity in vitro and in vivo, with low toxicity, which indicates its potential as an anticancer agent.